PENGEMBALIAN KEUANGAN NEGARA HASIL TINDAK PIDANA KORUPSI - Razak Musahib, Abd (Katalogis, 2015)
This is a juridical empirical research in combination with normative juridical. Based on the results of the study indicate that the assets of the proceeds of corruption is the right of the state to be returned to the state and the state that has the right to manage the assets and wealth of the country to be used for the greatest prosperity and welfare of the people. The Founding Father emphatically said that the purpose of Indonesia as stated in the fourth paragraph of the Preamble The Constitution of the Republic of Indonesia is to protect the people of Indonesia and the entire country of Indonesia, promote the general welfare, the intellectual life of the nation, and participate in the establishment of world order, based on freedom , lasting peace and social justice. In this theory is to give priority to the principle of expediency adding the state budget (Budget). Thus people will get in terms of usefulness, because the economy will increase. Ideally in a country that is based on state law (rechtstaat) commander law means what is stipulated in the law must be obeyed by all the people, but still far from the expectations of Indonesian nation, In essence, the return of the country's financial losses due to corruption is very important because obviously -clear contrary to the provisions of applicable law.